Vaginal Microbiota Changes in the Vulvar Lichen Simplex Chronicus - Ling Mei; Dongmei Wei; Yueyue Chen; Yueting Zhang; Tao Cui; Jian Meng; Xiaoli Zhang; Yuqing Liu; Lisha Ding; Qian Wang; Tao Wang; Xiaoyu Niu (IMR Press, 2023)
Background: The vulvar lichen simplex chronicus (VLSC) is a common condition in gynecologic clinics. Though VLSC is not life-threatening, it usually causes pruritus, soreness and dispareunia, which cause general discomfort. The exact etiology of VLSC is unclear. This study was performed to explore the vaginal microbiota of VLSC and to identify the possible microbial factors in attacks. Methods: Ninety women were recruited. 45 patients with VLSC and 45 women without vulvar symptom were identified as lichen simplex chronicus (LSC) and H groups respectively. The vaginal microbiota of the two arms were compared by the V3-V4 region of 16S rRNA sequencing. Results: The LSC group had less alpha diversity than H group (p < 0.05) and the beta diversity of LSC group was also distinct from the H group. Linear discriminant analysis effect size (LEfSE) analysis indicated that genus Sneathia and family Leptotrichiaceae were discriminant taxa in LSC group. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis found that microbial genes related to the signal transduction, metabolism of terpenoids and polyketides, transporters, nervous system, energy metabolism and others were different in the LSC and H groups. Conclusions: VLSC was associated with dysbioss of vaginal microbiota profiles compared with healthy control cases.